2015
DOI: 10.1007/s12013-014-0492-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols in Regulation of Redox Signaling and Inflammation During Cardiovascular Diseases

Abstract: Cardiovascular diseases remain one of the major health problems worldwide. The worldwide research against cardiovascular diseases as well as genome wide association studies were successful in indentifying the loci associated with this prominent life-threatening disease but still a substantial amount of casualty remains unexplained. Over the last decade, the thorough understanding of molecular and biochemical mechanisms of cardiac disorders lead to the knowledge of various mechanisms of action of polyphenols to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…AA is transformed into prostaglandin (PGE2), which is converted by COXs to eicosanoids (including prostaglandins and leukotrienes), which influence both innate and adaptive immunity [52,53]. The downregulation of COX-2 observed in this study could restrict prostanoid (prostaglandin, thromboxane and prostacyclin) production from AA.…”
Section: Discussionmentioning
confidence: 93%
“…AA is transformed into prostaglandin (PGE2), which is converted by COXs to eicosanoids (including prostaglandins and leukotrienes), which influence both innate and adaptive immunity [52,53]. The downregulation of COX-2 observed in this study could restrict prostanoid (prostaglandin, thromboxane and prostacyclin) production from AA.…”
Section: Discussionmentioning
confidence: 93%
“…Radical scavenger effects may be involved in the reaction with receptors or enzymes that are regulated by antioxidant response elements (e.g. Nrf2) that regulate the redox status in vivo, and some of the anticipated beneficial health effects of polyphenols are today suggested to be mediated through these mechanisms [74].…”
Section: Free Radicals and Antioxidant Activitymentioning
confidence: 99%
“…Polyphenols are found in plant-derived foods and beverages. Collective evidence has indicated that natural polyphenols possess multiple protective effects against cardiovascular diseases (Raj et al, 2014 ; Niu et al, 2015 ). Additionally, polyphenols classified to different subclasses have been reported to alleviate cardiac dysfunction and fibrosis following cardiac injury.…”
Section: Introductionmentioning
confidence: 99%